Bacteriophobic Zwitterionic/Dopamine Coatings for Medical Elastomers. Issue 30 (9th September 2022) - Texidó, Robert; Cabanach, Pol; Kaplan, Richard; García‐Bonillo, Cristina; Pérez, Darío; Zhang, Shuo; Borrós, Salvador; Pena‐Francesch, Abdon
Abstract: Despite modern advancements in sterilization and medical practices, bacterial infections remain a significant concern in the implantation of medical devices. There is currently an urgent need for long‐lasting and high‐stable strategies to avoid the adhesion of bacteria to the wide range of materials present in medical devices. Here, a versatile methodology to create anti‐biofouling coatings that prevent the adhesion of bacteria to silicone‐based materials used in healthcare is reported. These coatings consist of bifunctional ethylene glycol dimethacrylate as an anchor between a zwitterionic polymer (SBMA), which provides antifouling properties, and a polydopamine layer that operates as an interfacial binder, providing mechanical strength and strong adhesion to elastomeric substrates. The coatings exhibit superhydrophilic and anti‐biofouling properties, creating a strong "bacteriophobic effect" that leads to a >99% reduction in bacterial adhesion. This bacteriophobic coating is successfully implemented and validated in a commercial urinary catheter, reducing bacterial adhesion by 1–2 orders of magnitude and avoiding bacterial colonization to prevent catheter‐associated urinary tract infections. The results presented here demonstrate the versatility, durability, and scalability of the coating methodology for preventing bacterial adhesion in silicone elastomers, which can be easily applied to other elastomeric materials used in medical devices beyond urinary tract infection prevention. Abstract : A multilayer zwitterionic coating strategy is introduced to avoid bacterial colonization in medical elastomeric devices. The coating combines high mechanical stability and strong bonding to stretchable substrates with high hydrophilicity and antibiofouling properties. Bacterial adhesion on a coated urinary catheter is significatively reduced (2 orders of magnitude decrease from commercial devices) after incubation with uropathogenic bacteria.